2016
DOI: 10.1111/andr.12218
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic link between erectile dysfunction and systemic endothelial dysfunction in type 2 diabetic rats

Abstract: Men with type 2 diabetes mellitus (T2DM) and erectile dysfunction (ED) have greater risk of cardiovascular events than T2DM men without ED, suggesting ED as a predictor of cardiovascular events in diabetic men. However, molecular mechanisms underlying endothelial dysfunction in the diabetic penis explaining these clinical observations are not known. We evaluated whether the temporal relationship between ED and endothelial dysfunction in the systemic vasculature in T2DM involves earlier redox imbalance and endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…eNOS and nNOS uncoupling, measured indirectly as a decreased ratio of active dimers to inactive monomers, refers to a switch in the enzyme's activity from NO-producing to a predominantly superoxide-producing enzyme (Fostermann & Sessa 2012). Previous studies demonstrated eNOS uncoupling in the penis of T2DM rats (Musicki et al, 2016) and nNOS uncoupling in the rat penile arteries under conditions of insulin resistance (Sanchez et al, 2012). We now extend these findings to the erectile tissue of T2DM men with ED, showing that both eNOS and nNOS are uncoupled.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…eNOS and nNOS uncoupling, measured indirectly as a decreased ratio of active dimers to inactive monomers, refers to a switch in the enzyme's activity from NO-producing to a predominantly superoxide-producing enzyme (Fostermann & Sessa 2012). Previous studies demonstrated eNOS uncoupling in the penis of T2DM rats (Musicki et al, 2016) and nNOS uncoupling in the rat penile arteries under conditions of insulin resistance (Sanchez et al, 2012). We now extend these findings to the erectile tissue of T2DM men with ED, showing that both eNOS and nNOS are uncoupled.…”
Section: Discussionmentioning
confidence: 98%
“…The prototype NADPH oxidase NOX2/gp91phox possesses cytosolic subunits (p47phox, p67phox, or homologues) and membrane-bound subunits (gp91phox and p22phox), which form a functional enzyme complex upon activation (Brandes et al, 2014). Increased protein expression of NOX2 subunits has been demonstrated in the penis of T2DM rats (Long et al, 2012; Musicki et al, 2016) and mice (Nunes et al, 2015). We now report upregulated NADPH oxidase catalytic subunit gp91phox in the human T2DM penis, implying activated NADPH oxidase as a source of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that increased oxidative stress and NOS uncoupling are accepted as a mechanistic link between erectile dysfunction and systemic endothelial dysfunction in type DM (Musicki & Burnett, 2017;Musicki, Hannan, Lagoda, Bivalacqua, & Burnett, 2016). But NOS uncoupling and penile ROS levels have not been evaluated in this study.…”
mentioning
confidence: 92%
“…Alterations of the NO-cGMP signaling pathway have been implicated as a major pathomechanism for ED [ 1 ]. ED in diabetic, hypertensive, and hypercholesterolemic animals has been associated with downregulation of eNOS and nNOS expression in the penis, as well as impaired cavernosal relaxation [ 19 21 ]. Elevated oxidative stress has also been associated with ED, since superoxide anion can react with NO, reducing NO bioavailability [ 19 , 22 24 ].…”
Section: Introductionmentioning
confidence: 99%